Exploring the changes in functional connectivity of the limbic system in Patients with amnestic mild cognitive impairment treated by acupuncture based on fMRI - Yingmei, Han; Yijie, Li; Heng, Zhang; Ze, Feng; Weiqing, Li; Hanxi, Zhang; Ming, Yang; Bingyuan, Chu; Feng, Wang (Frontiers in Neurology, 2025)
ObjectiveBrain functional connectivity (FC) of Limbic system plays an important role in maintaining the normal cognitive state. We conduct an investigation of the FC of limbic system networks in amnestic mild cognitive impairment (aMCI) and speculate on the brain effect mechanism of acupuncture therapy based on resting - state Functional Magnetic Resonance Imaging (rs - fMRI).Method50 patients with aMCI and 41 healthy participants (HC group) from the First Affiliated Hospital of Heilongjiang University of Chinese Medicine in Harbin City, Heilongjiang Province, China, were recruited.rs-fMRI data of all participants were collected. Among them, 35 aMCI participants (true-acupoint group) were treated with the Yuanluo Tongjing acupuncture method for two courses of treatment (once a day, needling every 10 min, retaining the needles for 40 min, 6 days of treatment + 1 day of rest, 4 weeks as one course, and starting the second course after an interval of 2 weeks). 15 aMCI participants (sham-acupoint group) received sham acupoint acupuncture intervention, and the specific intervention details were the same as those of the true-acupoint group. After treatment, rs-fMRI data of aMCI subjects were collected again. Thirty seed points of the limbic system were selected based on the Anatomical Automatic Labeling (AAL) template, and the Statistical Parametric Mapping (SPM) software was used for statistical analysis of FC indices between and within groups.Result(1) Compared with the HC group, there were significant differences in the FC between Seed14 of the true-acupoint group before acupuncture intervention and multiple brain regions (enhanced with Seed 7 and weakened with Seed 15). There were differences in the FC of Seed4, Seed29, and Seed30 in the sham-acupoint group, indicating that there were baseline differences among aMCI patient groups. (2) After acupuncture in the true-acupoint group, the FC between multiple seed points and brain regions decreased, while the differences before and after the intervention in the sham-acupoint group mostly did not pass the Family-Wise Error (FEW) correction. (3) Compared with the HC group, the FC of seed points in both the true-acupoint group and the sham-acupoint group mainly decreased after acupuncture. The true-acupoint group involved a wider range of brain regions (the middle frontal gyrus, the left medial superior frontal gyrus, the middle part of the left cingulate gyrus and the gyri surrounding its lateral side, the gyri below the bilateral parietal bones except the supramarginal gyrus and the angular gyrus, the precuneus, etc.). (4) The FC between Seed14 and the left superior frontal gyrus medialis (Seed7), as well as the right caudate nucleus of the true-acupoint group was enhanced before acupuncture and decreased after acupuncture, which may serve as an observational indicators for the intervention of aMCI by acupuncture at acupoints. (5) The Montreal Cognitive Assessment (MoCA) score is more representative in characterizing the abnormal FC between brain regions in aMCI patients.ConclusionThe cerebral effect mechanism of acupuncture at acupoints for aMCI is more complex. It can regulate the functional connections within the limbic system and between the limbic system and other brain regions, mainly manifested as a decrease. Among them, the FC among Seed17-Parietal_Inf_L, Seed25-Frontal_Mid_L, and See25-Frontal_Sup_Medial_L has become a statistically significant detection index.